2006
DOI: 10.1111/j.1460-9568.2006.04775.x
|View full text |Cite
|
Sign up to set email alerts
|

Both α2 and α3 GABAA receptor subtypes mediate the anxiolytic properties of benzodiazepine site ligands in the conditioned emotional response paradigm

Abstract: Mice with point-mutated alpha2 GABAA receptor subunits (rendering them diazepam insensitive) are resistant to the anxiolytic-like effects of benzodiazepines (BZs) in unconditioned models of anxiety. We investigated the role of the alpha2 GABAA subtype in a model of conditioned anxiety. alpha2(H101R) and wildtype mice were trained in a conditioned emotional response (CER) task, in which lever-pressing for food on a variable interval (VI) schedule was suppressed during the presentation of a conditioned stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 46 publications
2
68
0
Order By: Relevance
“…α2 −/− mice (31) and α2H101R "knock-in" mice (11,12) were gen- Locomotor Activity. Locomotor activity, and behavioral sensitization to cocaine (α2 −/− ) mice or Ro 15-4513 (α2H101R) mice were measured in circular runways, as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…α2 −/− mice (31) and α2H101R "knock-in" mice (11,12) were gen- Locomotor Activity. Locomotor activity, and behavioral sensitization to cocaine (α2 −/− ) mice or Ro 15-4513 (α2H101R) mice were measured in circular runways, as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the point mutation does not alter the sensitivity of the receptor to its natural ligand, GABA. As selective ligands for α2-containing receptors are not available, we used this knowledge to differentially facilitate transmission at α2-containing receptors, using knock-in mice (11,12) in which the normal H at position 101 within the benzodiazepine binding pocket of the α2 protein was replaced by R (α2H101R mice). In such mutant mice, Ro 15-4513 will continue to act as an inverse agonist at α1−, α3−, and α5-containing receptors, and as an agonist at α4-and α6-containing receptors, so that the only difference between WT and mutant mice will be the direction of Ro 15-4513s action at α2-containing receptors.…”
Section: Cocaine Effects In α2mentioning
confidence: 99%
“…This approach has been applied to several pentameric ligand-gated ion channels and has been quite successful in linking specific receptor subunits with drug actions. One of the earliest and most elegant Ligand-Gated Ion Channel Alcohol Sites examples is the construction of knock-in mice with specific GABA A receptor subunits lacking actions of benzodiazepines or general anesthetics (Rudolph and Möhler, 2004;Morris et al, 2006;Tan et al, 2011). For example, these studies showed that benzodiazepine modulation of the a2 subunit of the GABA A receptor is critical for the antianxiety actions of these drugs and the general anesthetic action of propofol is due to action on GABA A receptors containing the b3 subunit (Jurd et al, 2003).…”
Section: A Behavioral Pharmacology In Rodent Modelsmentioning
confidence: 99%
“…Gamma-aminobutyric acid (GABAA) receptors had been widely studied since they are the site of action of a number of clinically important drugs, including benzodiazepines, barbiturates, and anesthetics (Morris et al, 2006). Benzodiazepines are the first-line drugs for the treatment of anxiety disorders, acting at the GABAA receptors which remain primary targets for novel anxiolytic compounds.…”
Section: Introductionmentioning
confidence: 99%